HUBUNGAN ANTARA FLAT FOOT DAN KESEIMBANGAN DINAMIS PADA ANAK SEKOLAH DASAR - Sigit Rachmad Setyawan (2023)
Background: The strong and elastic connections of ligaments, tendons and fascia between the forefoot and hindfoot help children's feet build their arches. The arch has a structure and dynamics that absorbs pressure, transmits body weight and acts as a lever as the body moves to propel it forward. Purpose: To find out whether there is a relationship between flat foot and body dynamic balance in elementary school children. Flat feet result from a low or absent medial longitudinal arch. Research on "The Relationship between Flat Foot and Dynamic Balance in Elementary School Students". Method: the research method used is correlational quantitative with a cross sectional approach. As many as 98 students of Limo 01 State Elementary School participated in this study, the parameters used were the Wet Footprint Test and Clarke's Angle to determine the degree of foot arch and the Balance Beam Test to measure Dynamic balance. The results of the flat foot frequency distribution using Clarke's angle respondents who have flat feet are 76 respondents (100%), the average is 11.61 ± 7.12, on the value of the balance beam of respondents by falling from the beam before completing the balance beam as many as 42 respondents (55.3 %), Results: the results obtained between flat foot and dynamic balance have a sig value of 0.002, where a p <0.05 results show that there is a relationship between the two variables so that H1 is accepted. Conclusion: there is a significant relationship between flat foot and dynamic balance